Potent leishmanicidal and antibacterial metabolites from Olea ferruginea. Issue 7 (3rd July 2019) - Zafar, Salman; -Ur-Rehman, Faiz; Shah, Zafar Ali; Rauf, Abdur; Khan, Aziz; Humayun Khan, Muhammad; Ur Rahman, Khaliq; Khan, Serab; Ullah, Abid; Shaheen, Farzana
Abstract: Inspired from the leishmanicidal and antibacterial potential of the fractions obtained from the crude extract of Olea ferruginea stem, the anti-leishmanial ethyl acetate fraction was subjected to chromatographic separation, leading to the isolation of a new compound ferruginan (1 ) and a known compound (+)- cycloolivil (2 ). The structures of1 and2 were determined by various spectroscopic techniques and were assayed for their in vitro antibacterial and leishmanicidal potential. Compound1 showed 75% inhibition after 24 h of incubation and 98% inhibition after 48 h of incubation against Leishmania tropica KWH23 promastigotes at 100 μg/mL concentration, while compound2 exhibited 73% and 96% inhibition at the same concentration and incubation time. Compound1 also showed good activity against various bacterial pathogens. Abstract :